Introducing Cu(II) onto SiO2-TiO2 with Rice Husk Ash as the Source of Silica and Its Catalytic Activity for Kumada Cross-coupling Reaction to Produce Biphenyl Compound - Agustiningsih, Dewi; Nuryono, Nuryono; Santosa, Sri Juari; Kunarti, Eko Sri (Indonesian Journal of Chemistry, 2025)
This research studied the preparation of SiO2-TiO2/Cu(II) by utilizing rice husk ash as the SiO2 precursor, and evaluated its efficiency as a heterogeneous catalyst in biphenyl synthesis through Kumada cross-coupling reaction, which is widely known as an important intermediate in pharmacology and agriculture manufacturing. In this study, the catalyst preparation was conducted by extracting SiO2 from rice husk ash, combining it with TiO2, and introducing Cu(II) onto its surface with CuCl2·2H2O as the precursor with various concentration of Cu(II). Comprehensive characterization using techniques such as IR, XRD, XRF, DLS, N2 isotherm adsorption-desorption, ICP-AES, STEM-EDS, TEM, UV-vis spectrometry, and TGA was conducted to examine the catalyst properties. Catalyst activity was evaluated in the Kumada cross-coupling reaction, using phenylmagnesium bromide and bromobenzene as reactants under stirring-heating condition, and the products were analyzed using GC-FID method. The characterization results indicated that the preparation of SiO2-TiO2/Cu(II) materials was successfully conducted and Cu(II) was formed as Cu(OH)2. The catalyst considerably promoted the Kumada cross-coupling reaction with a biphenyl yield of 78.85% at 50 °C for 6 h under stirring-heating method. Furthermore, catalyst reusability test demonstrated that the catalyst sustained performance over three cycles without losing its activity significantly. Interestingly, SiO2-TiO2 was observed to function primarily as support material and adsorbent, immobilizing Cu(II) and enhancing reactant reduction but not directly influencing biphenyl formation. Overall, this study contributes to the understanding of SiO2-TiO2/Cu(II) catalyst preparation and its application in biphenyl synthesis, offering insights into catalyst design and performance optimization for future applications in organic synthesis.